2014
DOI: 10.1002/anie.201408648
|View full text |Cite
|
Sign up to set email alerts
|

Superhalogens as Building Blocks of Halogen‐Free Electrolytes in Lithium‐Ion Batteries

Abstract: Most electrolytes currently used in Li-ion batteries contain halogens, which are toxic. In the search for halogen-free electrolytes, we studied the electronic structure of the current electrolytes using first-principles theory. The results showed that all current electrolytes are based on superhalogens, i.e., the vertical electron detachment energies of the moieties that make up the negative ions are larger than those of any halogen atom. Realizing that several superhalogens exist that do not contain a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
150
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(156 citation statements)
references
References 40 publications
6
150
0
Order By: Relevance
“…[12][13][14][15] There are a number of limitations of the conventional ionic liquid electrolytes that need to be tackled to improve the safety and performance of lithium-ion batteries. 16,17 (1) Most of the ionic liquid electrolytes contain halogenated anions such as BF 4 À , PF 6 improving the safety and performance of the batteries. Some other orthoborate-based lithium salts that are not aromatic have been extensively investigated for their applications in lithium batteries.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] There are a number of limitations of the conventional ionic liquid electrolytes that need to be tackled to improve the safety and performance of lithium-ion batteries. 16,17 (1) Most of the ionic liquid electrolytes contain halogenated anions such as BF 4 À , PF 6 improving the safety and performance of the batteries. Some other orthoborate-based lithium salts that are not aromatic have been extensively investigated for their applications in lithium batteries.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Metal closo-borates are salts with polyhedral B n H n 2À (n = 6-12) anions, among which the salts of the B 10 H 10 2À and B 12 H 12 2À anions were early noted due to their high thermal and chemical stability. 13 LiCB 11 H 12 as a halogen free electrolyte was also predicted by theory 14 and used in experiments to synthesize a Mg-electrolyte. 15 closo-Borate and related carborate salts (with monovalent CB nÀ1 H n À anions) also exhibit structural transitions to highly conductive phases, above room temperature.…”
mentioning
confidence: 99%
“…In addition to numerous applications of superhalogens, we have recently pointed out their possible usage as strong oxidizing agents [18][19][20][21] and Lewis-Brønsted superacid precursors [7,22, 23]. It should also be mentioned that some recent works revealed novel superhalogen applications in Li-ion batteries, solar cells, and hydrogen storage materials [24][25][26][27].It was also established that one of the important features characterizing superhalogen anions is their tendency to adopt high-symmetry compact structures [10]. Recent report concerning the properties of the Li n F − n+1 (n = 2-5) superhalogen anions confirmed that observation, as the Abstract Polynuclear superhalogen anion Li 12 F 13 − and its ionic complexes formed by the interaction with selected metal ions (i.e., Li 12 F 13 − Na + , Li 12 F 13 − K + , Li 12 F 13 − Mg 2+ , and Li 12 F 13 − Zn 2+ ) are proposed and investigated on the basis of ab initio calculations.…”
mentioning
confidence: 99%
“…In addition to numerous applications of superhalogens, we have recently pointed out their possible usage as strong oxidizing agents [18][19][20][21] and Lewis-Brønsted superacid precursors [7,22, 23]. It should also be mentioned that some recent works revealed novel superhalogen applications in Li-ion batteries, solar cells, and hydrogen storage materials [24][25][26][27].…”
mentioning
confidence: 99%